Analysis of chronic physiological demand of an annual soccer season - Daniel Barbosa Coelho; Eduardo Mendonça Pimenta; Rodney Coelho da Paixão; Rodrigo Figueiredo Morandi; Lenice Kappes Becker; João Batista Ferreira-Júnior; Leonardo Gomes Martins Coelho; Emerson Silami-Garcia (Universidade Federal de Santa Catarina, 2015)
Exercise intensity monitoring has been essential for the control and planning of sports training. Thus, the aim of the present study was to assess the chronic physiological demand of soccer players during an annual soccer season using blood biomarkers. Ten professional soccer players (21.2 ± 3.7 years) participated in this study. Blood samples were collected on the day before beginning of preseason (C1); at the end of preseason and beginning of competitive calendar (C2); and at the end of the competitive calendar. Interleukin-6 (IL-6), cortisol, testosterone, testosterone/cortisol ratio, creatine kinase and alpha-actin were evaluated. Statistical analysis was performed by using ANOVA with repeated measures and the post-hoc Tukey's test. Significance level was set at P<0.05. The results showed significant differences in the following situations: testosterone - C1 higher than C2 and C3; cortisol - C3 higher than C2; testosterone/cortisol ratio - C2 higher than C1, and C3 lower than C1 and C2; creatine kinase - C2 and C3 higher than C1; alpha-actin - C3 higher than C1. IL-6 concentrations were not different between C1, C2 and C3. It could be concluded that an annual soccer season imposes high physiological demand for professional players, since relevant changes in blood biomarkers analyzed were observed.